The Impact of Chatbot Type and Student Motivation on Academic Efficiency in Educational Technology - Abdelrhman, Shaymaa Ahmed Ahmed Mohamed; AbouHashesh, Mohamed Radwan Ibrahim; Kahouf, Samir Ahmed Elsayed (Journal of Posthumanism, 2024)
This study investigates how student motivation (high vs. low) and chatbot type (rule-based vs. deep learning-based) affect academic performance among students enrolled in educational technology programs. Knowing how well various chatbot technologies work is essential given the growing use of AI in education. As conversational agents, chatbots improve the learning process by offering real-time feedback, tailored assistance, and ongoing interaction. The study assesses deep learning-based chatbots, which use sophisticated machine learning algorithms for more adaptive interactions, and rule-based chatbots, which operate using predetermined rules and structured scripts. Furthermore, as a moderating element in chatbot efficacy, student motivation—a crucial determinant of academic success—is investigated. Surveys and performance evaluations of students enrolled in educational technology programs were used to gather data. The association between chatbot type, student motivation, and academic effectiveness was examined using statistical techniques such as regression analysis and ANOVA. Results show that, especially for highly driven students, deep learning-based chatbots considerably increase academic efficiency when compared to rule-based chatbots. The relationship between motivation and chatbot type implies that AI-powered tailored learning strategies can better meet the needs of a wide range of students. For educators, instructional designers, and legislators looking to use AI technologies to enhance education, these findings have important ramifications. Future studies should investigate other factors that affect chatbot efficacy and provide customized approaches for diverse learning environments.